Juvenile ossifying fibroma of the orbit: a rare location - Clarós, Pedro; Polainas, Sofia; Fortuny, Marta; Clarós, Andres (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Osseous tumors in the craniofacial skeleton of young patients are not very frequent, and tumors involving the walls of the orbital cavity are even more infrequent. Despite being usually slow-growing, even small neoformations can have a local aggressive behavior, displacing and compressing vital structures, and so it is important to perform an early diagnosis in order to avoid the tumor to pose problems on the optic nerve and threaten vision. The case that we are presenting shows an ossifying fibroma in a 19-year-old male from Ethiopia, a benign lesion whose progressive growth caused proptosis and downward displacement of the left eye. Following an adequate radiological diagnosis, we were able to delimit the fibroma existence and location. The surgery was conducted in a conservative form, allowing the patient not to suffer from post-surgery malformations. Histopathological diagnosis was compatible with juvenile ossifying fibroma, psammomatoid variant, arising from an uncommon location – the roof of the orbit.